Caracterização hidrossedimentométrica de uma pequena bacia hidrográfica e balanço sedimentométrico no reservatório do Vacacaí Mirim - Teixeira, Laís Coelho (2015)
The sediment yield causes a number of problems, and among them stands out silting of rivers and reservoirs, and contamination of surface water. Sediments result from the processes of erosion, transport, storage and compression. They depend on the physical characteristics of the watershed, as well as soil use and land cover. To study the sediment yield of a river is important to estimate the amount and origin of the sediments transported and deposited in a watershed. Therefore, it is possible to obtain knowledge about the unit of study, which leads to better planning and use of water resources. From liquid and solid discharge measurements in a river section, and conducting a sedimentometrical balance in Vacacaí Mirim reservoir, located at Santa Maria, Rio Grande do Sul, Brazil, the objective of this research is to characterize the sediment yield of a small watershed. The methodology was based on two stages: the first one was about the sedimentometrical characterization of the study area, and it was carried out between January and November of 2014, with the continuous monitoring of flow and sediments in fluviossedimentometrical station João Goulart, whose laboratory samples were also characterized and had their sediment concentration determined; the second stage was about the execution of sedimentometrical balance in the reservoir with the help of HEC-HMS 4.0 modeling program. Sediment entries, storage and output were checked in Vacacaí Mirim reservoir, which influences the study area. The results for the hydrossedimentometrical monitoring were satisfactory, getting a key curve with determination coefficient of 0.96; sedimentometrical curves ranged from 0.93 to 0.98; concentration ratio between suspended sediment and turbidity was 0.84, being considered acceptable; particle size characteristics were predominantly silt, for suspended material, and sand, for dragged material. Balance calibration for sedimentometrical hydrologic model gave a Nasch-Sutcliffe between 0.13 to 0.53 and 0.44 in validation; about reservoir sediments balance, it was noted and therefore considered that all sediment that enters the reservoir is retained and more sediment is produced downstream thereof mouth of the river it reaches the watershed.